2015
DOI: 10.1021/mp500875f
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopamine-Loaded Core-Cross-Linked Polymeric Micelles Enhance Radiation Response in Pancreatic Cancer and Pancreatic Stellate Cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers. Cyclopamine (CPA), a potent inhibitor for sonic hedgehog pathway (SHH), shows great promises in PDAC treatment, including the disruption of tumor-associated stroma, and enhancement of radiation therapy. However, CPA is insoluble in water; therefore requires a nanometric delivery platform to achieve satisfactory performance. We herein encapsulated CPA in a core-crosslinked polymeric micelle system (M-CPA). M-CPA was combined with Cs-137 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Because SHH inhibitors used at high doses might have caused significant systemic toxicity and possible off-target effects, we argued that the benefits of SHH inhibition in PDAC treatment should not be completely ruled out [13]. Numerous preclinical studies had shown that treatment with SHH inhibitors, e.g., cyclopamine (CPA) and IPA-926 (saridegib, a semisynthetic derivative of CPA), could increase tumor vasculature [14], sensitize tumor cells to radiotherapy [15], and deplete cancer stem cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Because SHH inhibitors used at high doses might have caused significant systemic toxicity and possible off-target effects, we argued that the benefits of SHH inhibition in PDAC treatment should not be completely ruled out [13]. Numerous preclinical studies had shown that treatment with SHH inhibitors, e.g., cyclopamine (CPA) and IPA-926 (saridegib, a semisynthetic derivative of CPA), could increase tumor vasculature [14], sensitize tumor cells to radiotherapy [15], and deplete cancer stem cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that overexpression of Hh signaling genes is linked to radiation resistance, and downregulation can enhance radiation responses in many tumor types including pancreatic, anaplastic thyroid, esophageal, and non-small cell lung cancers [11-14]. In addition, several clinical studies have shown a positive correlation between overexpression of Hh signaling genes and poorer outcomes of various kinds of cancer [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the response of PDAC to ionizing radiation (IR), Zhao et al. 55 combined CPA-loaded core-crosslinked polymeric micelles (M-CPA) with Cs-137 radiation to enhance the radiation cytotoxicity of Cs-137. In their results, M-CPA treatment can decrease the number of CAFs, intimating that M-CPA may disrupt the tumor-associated stroma in vivo , thus relieving the hypoxia condition within the tumor microenvironment.…”
Section: Natural Products Normalize Ecmmentioning
confidence: 99%